EFFECT OF AGRICULTURE SITES AND GROWTH STAGES ON PHYSICAL AND CHEMICAL PROPERTIES ON DATE PALM Phoenix - M.Sh. Abdul-Wahed (University of Thi-Qar Journal of Science, 2019)
This study was conducted in three sites of basrah fields (Hartha, Shutt Al-Arab and Abu-Alkhasseb ,during the growing season 2002 , to vestigated the agriculture site on physical and chemical properties ofdate palm fruits cv . khentar at the Chemri ,Khalal and Rutab stages ,The results showed that the site was hada significant effect on physical and chemical properties of date palm cv. Khentar .So the statistical analysisresults showed that there were a significant difference among sites in physical and chemical properties ofdate palm fruit in Abu-Alkhaseb site had significant effect compaire with other sites